INTEGRASI NILAI-NILAI KARAKTER ISLAMI DALAM PEMBELAJARAN BAHASA ARAB - Hairus Sodik; Moh. Anwar (Al-Usthurah, 2026)
The development of globalization and advances in technology have brought significant impacts on the character formation of the younger generation, including within Islamic education. One of the main challenges is the weakening of students’ moral and spiritual values. This article aims to conceptually and through a literature review examine the integration of Islamic character values in Arabic language learning. This study employs a qualitative approach using the library research method on books, journal articles, and relevant scientific publications from the last five years. The findings indicate that Arabic has strategic potential as a medium for character education due to its position as the language of the Qur’an and Hadith. Value integration can be carried out through the selection of value-laden teaching materials, reflective–communicative learning methods, teachers’ role modeling, and holistic evaluation. However, challenges remain, including the dominance of technical–linguistic approaches, limited teaching materials, low pedagogical competence in value education, and weak character evaluation systems. Therefore, a reorientation of learning objectives, strengthening teacher capacity, and developing affective assessment systems are needed so that Arabic language learning can function optimally as a medium for Islamic character formation.